2011
DOI: 10.1097/mao.0b013e31821a8407
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors Influencing Educational Placement of the Hearing-Impaired Child With a Cochlear Implant

Abstract: Our results show that parental education, a variable that the health system cannot control, significantly influences postimplantation results in term of educational placement and can thus limit the chances of implanted children to achieve mainstream placement even when identified and implanted at an early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 33 publications
(25 reference statements)
1
31
2
Order By: Relevance
“…29 30 31 As for education level of the caregiver in this study, 56.67% of the subjects had completed high school, followed by those with higher education (20%). Yehudai et al 32 state that the socio-demographic parameter, highlighting parental education, a variable that the health system cannot control, significantly influences the results after implantation, since accessibility to speech sounds, achieved after CI activation, must be integrated with the possibilities of stimulation available in the environment throughout the process (re)habilitation. Thus, the education level of the caregiver may limit the chances of the implanted child achieving the expected performance, even when identified and implanted at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…29 30 31 As for education level of the caregiver in this study, 56.67% of the subjects had completed high school, followed by those with higher education (20%). Yehudai et al 32 state that the socio-demographic parameter, highlighting parental education, a variable that the health system cannot control, significantly influences the results after implantation, since accessibility to speech sounds, achieved after CI activation, must be integrated with the possibilities of stimulation available in the environment throughout the process (re)habilitation. Thus, the education level of the caregiver may limit the chances of the implanted child achieving the expected performance, even when identified and implanted at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, a larger amount of concrete and visual resources are necessary to minimize learning difficulties (24,31) . Reports in the literature show that lexical development can be influenced by family income and by the number of schooling years that the parents have (8,22) . In this study, we found no association between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found no association between these variables. However, it is known that verbal models, provided by the environment, can influence language development by their quantity, quality, and relations to situations faced by the child (22) . A study carried out in Brazil shows that families with high per capita incomes and more schooling years, including post-secondary school, tend to use more complete sentences by using more syntactic variations and better grammatical complexity, which positively influences oral language development (8) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations